A sedimentological oxymoron: highly evolved glauconite of earliest diagenetic origin - Tribovillard, Nicolas; Bout-Roumazeilles, Viviane; Guillot, François; Baudin, François; Deconinck, Jean-François; Abraham, Romain; Ventalon, Sandra (Comptes Rendus. Géoscience)
This work examines the possibility of a rapid formation of glauconite in a relatively shallow platform environment (below fair-weather wave baseline). The materials studied here are uppermost Jurassic alternations of carbonate beds and marly interbeds, namely, the Assises de Croï Formation of the Boulonnais area (northernmost France). The carbonate beds yield field evidences of an early diagenetic origin and both beds and interbeds contain glauconite, questioning the duration of formation of the glauconite, relative to that of the diagenetic carbonate beds. Carbon and oxygen stable isotope composition of the carbonate beds confirm an early diagenetic growth. Contrasted grain-size distribution patterns of glauconite and quartz grain populations (isolated after acid digestion and magnetic separation) evidenced that glauconite formed after sediment deposition. Glauconite formation allegedly requires protracted episodes of ion capture from the water column, which is no longer possible when glauconite gets trapped within authigenic carbonates. Therefore, in-situ glauconite formation preceded carbonate authigenesis. Yet, the chemical composition of grains (Fe and K) typifies glauconite as highly evolved, meaning that its formation must have lasted over times, according to conventional views. Consequently, our results challenge these conventional views and confirm that glauconite can form in relatively shallow environments (which has been already brought to light previously) and it is concluded that early diagenetic glauconite can be markedly enriched in both K and Fe, which is an unprecedented result.